Canceling Interference in Acupuncture Points Signal - Yanexy San Martín Reyes (Revista Cubana de Ingeniería, 2012)
The present paper propose the cancellation of interference or artifacts by the method of Allen in signals captured in different acupuncture points (Small Intestine Meridian, points ID1-ID2 and ID1-ID19). It is considered that the biosignal under study should be able to be characterized after its acquisition by subtracting the different interference variables that may coexist in the measurement zone, as it is in the case of ECG or any other artifact. The biosignal obtained as a result of the cancellation will be the acupuncture signal or from its imperfection another wave can be obtained as from a bioelectrical point of view such imperfection can be characterized and at the same time can bb useful to establish a long-term correspondence between the behavior of the signals on various acupuncture points and different diseases.